High-dose thiamine as initial treatment for Parkinson's disease. (28th August 2013) - Costantini, Antonio; Pala, Maria Immacolata; Compagnoni, Laura; Colangeli, Marco
Abstract : Parkinson's disease (PD) is a systemic disease with motor and non-motor deficits. We recruited three patients with newly diagnosed PD. They were not under anti-Parkinson's therapy. Plasmatic thiamine was within healthy reference range. We performed the Unified Parkinson's Disease Rating Scale (UPDRS) and started a parenteral therapy with high doses of thiamine. The therapy led to a considerable improvement in the motor part of the UPDRS ranging from 31.3% to 77.3%. From this clinical observation, it is reasonable to infer that a focal, severe thiamine deficiency due to a dysfunction of thiamine metabolism could cause a selective neuronal damage in the centres that are typically hit in this disease. Injection of high doses of thiamine was effective in reversing the symptoms, suggesting that the abnormalities in thiamine-dependent processes could be overcome by diffusion-mediated transport at supranormal thiamine concentrations.